VEGF, BFGF \& ENDOSTATIN DO NOT PREDICT PROGNOSIS IN HEPATOCELLULAR CARSINOMA PATIENTS - Sykymbayev, A.; Eren, F.; Tiftikci, A.; Tuere, F.; Guenduez, F.; Ozdogan, O. (ELSEVIER SCIENCE BV, 2010)
45th Annual Meeting of the European-Association-for-the-Study-of-the-Liver, Vienna, AUSTRIA, APR 14-18, 2010